Critical survey of stability constants of EDTA complexes : critical evaluation of equilibrium constants in solution ; part A: stability constants of metal complexes - Anderegg, G. (IUPAC chemical data series ;, 1977)
Critical Survey of Stability Constants of EDTA Complexes focuses on the computations, values, and characteristics of stability constants. The book emphasizes that for a critical discussion of experimentally determined stability constants, it is important to consider the precision of the values that manifests the self-consistency of the constant, taking into consideration the random errors. The publication reviews the stability constants of metal complexes. The numerical calculations affirm the reactions and transformations of metal ions when exposed to varying conditions. The text also present.